(Un)Commonly Connected: A Social Network Analysis of State Standards Resources for English/Language Arts. (November 2016) - Hodge, Emily M.; Salloum, Serena J.; Benko, Susanna L.
As states continue to implement the Common Core State Standards (CCSS), state educational agencies (SEAs) are providing professional development and curricular resources to help districts and teachers understand the standards. However, little is known about the resources SEAs endorse, the states and/or organizations sponsoring these resources, and how states and organizations are connected. This study investigates the secondary English/language arts resources provided by 51 SEAs (2, 023 resources sponsored by 51 SEAs and 262 intermediary organizations). Social network analysis of states and sponsoring organizations revealed a core-periphery network in which certain states and organizations were frequently named as the sponsors of resources, while other organizations were named as resource sponsors by only one state. SEAs are providing a variety of types of resources, including professional development, curriculum guidelines, articles, and instructional aids. This study offers insight into the most influential actors providing CCSS resources at the state level, as well as how SEAs are supporting instructional capacity through the resources they provide for teachers.